Migration Problem: Reasons, Impacts and Way to Overcome - Afroje, Sahariya; Ashik, Syod Ahsanul Islam (Advances in Social Sciences Research Journal, 2023)
The world is currently confronted with multidimensional challenges, migration problem, more specifically, illegal migration, is one of the most remarkable among them. People are being migrated to relatively safe, secure, and prosperous places from unsafe, insecure and poorer places either for better income, better life, better education or for security purpose. Whatever reason, migration, mostly the illegal migration are creation enormous problems in both the home countries and the host countries. The aim of the study is to analysis the reasons for the growing rate of migration, its impacts, and potential ways to overcome the challenges. The study is mainly based on secondary sources of data and information including scientific and academic journals, scholar articles, research papers, books, and other relevant sources to make a deep analysis. The study recommends ‘Absolute Globalization’, an absolute integration of global economic, education, political, and social institutions where regionalism will be the cornerstone of the integration, as the way to confront the challenges.